2023
DOI: 10.1210/clinem/dgad181
|View full text |Cite
|
Sign up to set email alerts
|

Bethesda III and IV Thyroid Nodules Managed Nonoperatively After Molecular Testing With Afirma GSC or Thyroseq v3

Abstract: Context Molecular testing has improved risk stratification and increased non-operative management for patients with indeterminate thyroid nodules, but data on the long-term outcomes of current molecular tests Afirma Gene Sequencing Classifier (GSC) and Thyroseq v3 are limited. Objective To determine the rate of delayed operation and the false-negative rate of the Afirma GSC and Thyroseq v3 in Bethesda III and IV thyroid nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The included studies had a total of 6490 FNAs with ITN cytology with molecular diagnostics (GEC, GSC, TSv2, and TSv3). The detailed characteristics of the included studies ( 9 , 10 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ) are given in Supplementary Table 3. According to the QUADAS-2 tool ( 24 , 25 ), the methodological quality of the included trials was acceptable ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies had a total of 6490 FNAs with ITN cytology with molecular diagnostics (GEC, GSC, TSv2, and TSv3). The detailed characteristics of the included studies ( 9 , 10 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ) are given in Supplementary Table 3. According to the QUADAS-2 tool ( 24 , 25 ), the methodological quality of the included trials was acceptable ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis that included 12 validation and real-world experience studies that reported the performance of Thyroseq (530 nodules) and Afirma (471 nodules) also showed comparable results [28]. Other studies comparing both tests have also found very similar performances between the two tests in terms of NPV, PPV, benign call rate, and clinical utility [12,29,34,35].…”
Section: Comparison Of Molecular Tests and Cost-effectiveness Conside...mentioning
confidence: 87%
“…Primarily, FCM application may be conceived in nodules with indeterminate cytological features. These in fact represent a growing clinical problem and molecular testing is proposed to improve the diagnostic accuracy of FNA and to reduce the need for diagnostic surgery [23]. To assure the adequacy of the sample, the rapid on site evaluation (ROSE) has been suggested [24]; however, the need for additional human resources limits the routine use of this approach.…”
Section: Discussionmentioning
confidence: 99%